Controlling the nutritional status score: a new tool for predicting postoperative mortality in patients with infrarenal abdominal aortic aneurysm treated with endovascular aneurysm repair - Sheng-Lin Ye; Tian-Ze Xu; Chuang Wang; Kang Han; Xu-Dong Jiang; Tao Tang; Bin Song; Xiao-Long Du; Nan Hu; Xiao-Qiang Li (Frontiers in Nutrition, 2024)
BackgroundAAA is a fatal condition that commonly occurs during vascular surgery. Nutritional status exerts a significant influence on the prognosis of various pathological conditions Scores from the CONUT screening tool have been shown to predict outcomes of certain malignancies and chronic diseases. However, the ramifications of nutritional status on AAA patients undergoing EVAR have not been elucidated in prior studies. In this study, we aimed to elucidate the correlation between CONUT scores and postoperative prognostic outcomes in patients with AAA undergoing EVAR.MethodsThis was a retrospective review of 177 AAA patients treated with EVAR from June 2018 to November 2019 in a single center. Patient characteristics, CONUT scores, and postoperative status were collected. These patients were stratified into groups A and B according to CONUT scores. Subsequently, a comparative analysis of the baseline characteristics between the two cohorts was conducted. Cox proportional hazards and logistic regression analyses were employed to identify the autonomous predictors of mid-term mortality and complications, respectively.ResultsCompared with group A, patients in group B had higher midterm mortality (p < 0.001). Univariate analysis showed that CONUT scores; respiratory diseases; stent types; preoperative Hb, CRP, PT, and Fb levels were risk factors for death. Multivariate analysis confirmed that CONUT score [HR, 1.276; 95% CI, 1.029–1.584; p = 0.027] was an independent risk factor for mortality. Logistic regression analysis showed that prior arterial disease, smoking, and D-dimer levels were risk factors, although multivariate analysis showed smoking (OR, 3.492; 95% CI, 1.426–8.553; p = 0.006) was an independent risk factor. Kaplan–Meier curves showed that patients in group B had shorter mid-term survival than those in group A (log-rank p < 0.001).ConclusionMalnutrition was strongly associated with mid-term mortality in patients with infrarenal AAA treated with EVAR.